Immunological evaluation of recombination PRRSV GP3 and GP5 DNA vaccines in vivo - Guanyu Zhao; Jiaqi Zhang; Wenchao Sun; Changzhan Xie; He Zhang; Yan Gao; Shubo Wen; Zhuo Ha; Fulong Nan; Xiangyu Zhu; Sheng Feng; Xinyu Cao; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The porcine reproductive and respiratory syndrome virus (PRRSV) is a threat to the health of pigs worldwide, but commercially available vaccines offer limited protection against PRRSV infection. It is necessary to develop a more effective DNA vaccine. The immunological effects of DNA vaccines with three adjuvants were examined in pigs (Susscrofa domestica) challenged with PRRSV. These DNA vaccines, which encoded PRRSV GP3 and GP5, were formulated with A1, A2, and A3. Serum specific and neutralizing antibodies, IL-4, IFN-γ, IL-2, IL-10, CD4+ and CD8+T-lymphocytes, health status, histopathology, and viral loads were determined. The results showed that the use of adjuvant A3 led to higher levels of neutralizing antibodies and a lower viral load in pigs compared to the other adjuvants. The neutralizing antibody titers of the pVAX-GP35+A1 and pVAX-GP35+A3 groups reached a peak of 1:19 at 35 dpi. The maximum concentration of IL-4 was 136.77 pg/mL in the pVAX-GP35+A3 group. At 35 dpi, the IFN-γ concentration in the pVAX-GP35+A1 group was 227.4 pg/mL. pVAX-GP35+A3 group shows the highest IL-2 and IL-10 expression to the peak of 597.6 pg/mL and 189.1 pg/mL, respectively. We found a formulation demonstrated beneficial immune outcomes. This study provides an alternative vaccine to protect pigs from PRRSV.